Pengaruh Pengangguran Terhadap Pertumbuhan Ekonomi Di Jawa Barat: Periode Tahun 2002-2023 - Maulania Rahma Azzahra; Siti Kumala Zahra; Jilan Rifa Fauziah; Hanivatul Husna; Laudza Hilmy; Dahri Tanjung; Disya Ayu Rivtryana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The unemployment situation in West Java remains a serious concern, particularly due to the impacts of the COVID-19 pandemic, technological changes, and industrial restructuring. During the transition period of the COVID-19 pandemic, the Open Unemployment Rate (TPT) in West Java Province decreased, indicating a potential relationship between unemployment rates and economic growth. This study aims to identify and analyze the effect of unemployment on economic growth in West Java using descriptive analysis and quantitative analysis with a multiple linear regression approach. Statistical analysis results show the regression equation Y = 6.170 – 0.088X1 – 0.771X2 + e. This means that if the variables unemployment (X1) and COVID (X2) are zero, economic growth (Y) remains constant at 6.170. Each 1% increase in unemployment reduces economic growth by 0.088%, while each 1% increase in COVID cases reduces economic growth by 0.771%. The F-test simultaneously, with a significance value of 0.000 < 0.05, indicates that the percentage of unemployment and the COVID dummy variable significantly affect economic growth in West Java. With an F value of 0.05, the alternative hypothesis (H1) is accepted, and the null hypothesis (H0) is rejected, indicating that unemployment and COVID variables significantly influence economic growth.